2018
DOI: 10.1073/pnas.1801889115
|View full text |Cite
|
Sign up to set email alerts
|

Structural homo- and heterosynaptic plasticity in mature and adult newborn rat hippocampal granule cells

Abstract: Adult newborn hippocampal granule cells (abGCs) contribute to spatial learning and memory. abGCs are thought to play a specific role in pattern separation, distinct from developmentally born mature GCs (mGCs). Here we examine at which exact cell age abGCs are synaptically integrated into the adult network and which forms of synaptic plasticity are expressed in abGCs and mGCs. We used virus-mediated labeling of abGCs and mGCs to analyze changes in spine morphology as an indicator of plasticity in rats in vivo. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 56 publications
11
62
0
Order By: Relevance
“…In the adult hippocampal dentate gyrus a tightly regulated transcription factor sequence that includes SOX11, generates new functional dentate granule neurons 22 24 . Adult-generated hippocampal DG neurons feature a highly stereotypic dendritic morphology, which is essential for DG neuron function and whose perturbation is associated with deficits in hippocampus-dependent information processing and behavior 25 29 . Having confirmed that SOXC transcription factor function is essential for neuronal differentiation in the adult neurogenic lineage 1 , we found that SOX11 and its S133 phospho-mutants were equally potent in rescuing the neuronal differentiation deficit of SoxC-deficient cells in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In the adult hippocampal dentate gyrus a tightly regulated transcription factor sequence that includes SOX11, generates new functional dentate granule neurons 22 24 . Adult-generated hippocampal DG neurons feature a highly stereotypic dendritic morphology, which is essential for DG neuron function and whose perturbation is associated with deficits in hippocampus-dependent information processing and behavior 25 29 . Having confirmed that SOXC transcription factor function is essential for neuronal differentiation in the adult neurogenic lineage 1 , we found that SOX11 and its S133 phospho-mutants were equally potent in rescuing the neuronal differentiation deficit of SoxC-deficient cells in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In introducing local synaptic heterogeneity, we picked ranges for Pfalse¯AMPAR and Pfalse¯GABAAR that satisfied the firing rate requirements above and picked values for Pfalse¯AMPAR and Pfalse¯GABAAR (for all synapses in the network) from independent uniform distributions spanning this range (Figure c). Such local synaptic heterogeneities could be consequent to baseline biological variability in presynaptic properties and postsynaptic receptor densities, differential dendritic processing of inputs owing to active and passive filtering, differential spine sizes consequent to the interaction between homo‐ and heterosynaptic spine plasticity and homeostatic regulation of overall synaptic drives (Aimone et al, ; Coulter & Carlson, ; Dieni et al, ; Dieni et al, ; Jedlicka, Benuskova, & Abraham, ; Jungenitz et al, ; Krueppel et al, ; Li et al, ; Mongiat, Esposito, Lombardi, & Schinder, ).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms behind the trafficking of several ion channels have been studied (Cusdin, Clare, & Jackson, ; Jensen, Rasmussen, & Misonou, ; Lai & Jan, ; Lau & Zukin, ; Lujan et al, ; Shah et al, ; Vacher et al, ; Wenthold, Prybylowski, Standley, Sans, & Petralia, ), and it is now clear that plasticity is ubiquitous (Kim & Linden, ). In addition to these changes in cytosolic and membrane proteins, it has been shown that hippocampal spines undergo continuous structural changes, apart from demonstrations of distinct forms of structural plasticity in spines, dendrites and axons (Attardo, Fitzgerald, & Schnitzer, ; Chen, Lu, & Zuo, ; Emoto, ; Engert & Bonhoeffer, ; Ghiretti & Paradis, ; Grubb & Burrone, ; Grubb & Burrone, ; Grubb et al, ; Ikegaya et al, ; Johnston et al, ; Jungenitz et al, ; Luo & O'Leary, ; Matsuzaki et al, ; Nagerl et al, ; Tonnesen et al, ; Yuste & Bonhoeffer, ). Finally, the dynamics associated with the various glial functions and their interactions with neuronal and metabolic pathways could also undergo changes in response to behavioral experiences and activity (Araque et al, ; Ashhad & Narayanan, 2019; Baumann & Pham‐Dinh, ; Fields, ; Halassa & Haydon, ; Haydon & Carmignoto, ; Khakh & Sofroniew, ; Pannasch & Rouach, ; Perea et al, ; Sierra, Tremblay, & Wake, ; Volterra, Liaudet, & Savtchouk, ).…”
Section: Degeneracy At Multiple Scales In the Hippocampusmentioning
confidence: 99%
“…The mechanisms behind the trafficking of several ion channels have been studied (Cusdin, Clare, & Jackson, 2008;Jensen, Rasmussen, & Misonou, 2011;Lai & Jan, 2006;Lau & Zukin, 2007;Lujan et al, 2009;Shah et al, 2010;Vacher et al, 2008;Wenthold, Prybylowski, Standley, Sans, & Petralia, 2003), and it is now clear that plasticity is ubiquitous (Kim & Linden, 2007). In addition to these changes in cytosolic and membrane proteins, it has been shown that hippocampal spines undergo continuous structural changes, apart from demonstrations of distinct forms of structural plasticity in spines, dendrites and axons (Attardo, Fitzgerald, & Schnitzer, 2015;Chen, Lu, & Zuo, 2014;Emoto, 2011;Engert & Bonhoeffer, 1999;Ghiretti & Paradis, 2014;Grubb & Burrone, 2010a;Grubb & Burrone, 2010b;Grubb et al, 2011;Ikegaya et al, 2001;Johnston et al, 2016;Jungenitz et al, 2018;Luo & O'Leary, 2005;Matsuzaki et al, 2004;Nagerl et al, 2004;Tonnesen et al, 2014;Yuste & Bonhoeffer, 2001).…”
Section: Degeneracy In the Induction And Expression Of Nonsynaptic mentioning
confidence: 99%